(untitled) (Research, Society and Development, 2023)
Pancreatitis is a common disease in felines, characterized by an infiltration of inflammatory cells in the exocrine portion of the pancreas. The main structural changes observed are fibrosis and necrosis. It presents with nonspecific clinical signs, including anorexia, lethargy, vomiting, abdominal pain, and diarrhea. Other clinical signs may be directly associated with comorbidities. Diagnosis can be made through histological findings, fPLI (feline pancreatic lipase immunoreactivity) levels, ultrasound, and clinical signs, although none of them has a sensitivity of 100%. Treatment for pancreatitis is supportive, focusing on symptom relief, fluid and electrolyte balance. The prognosis depends on the degree of involvement and the presence of associated comorbidities. This study aimed to analyze the profile and most common comorbidities in patients diagnosed with pancreatitis at a specialized feline veterinary hospital in Caxias do Sul. The methodology used was a retrospective study, collecting data from 21 feline patients treated between October 2021 and October 2022. The results showed a prevalence of 52.4% males, 80.95% neutered cats, and 80.95% mixed-breed cats. The most common comorbidity was inflammatory bowel disease (42.85%). The average age of the studied feline patients was 8.604 years (SD 5.36). There was a discrepancy regarding the comorbidity of diabetes mellitus, which is typically described as a major occurrence in cases of pancreatitis, as none of the animals in this study presented that condition.